Storytelling to Improve Speaking Skills - Siavichay-Márquez, Ana Cecilia; Guamán-Luna, Martha Magdalena (EPISTEME KOINONIA, 2022)
This study aims to establish the effectiveness of storytelling to increase the speaking skills of adolescent students at high school level; through, a mixed methods analysis using as data collection technique: the survey. This instrument was applied to tenth grade students of the Remigio Romero y Cordero Educational Unit in Cuenca. The survey was used to collect data to evaluate the impact of the oral expression activities and the students' perceptions, experiences, opinions and points of view. With these results obtained, a proposal emerges for the foreign language teachers of the Remigio Romero y Cordero Educational Unit in Cuenca, on the benefits of applying storytelling with adolescents, its effectiveness in improving the level of language proficiency and recommendations for its implementation in schools.